KEBIJAKAN DALAM PENENTUAN DAN PENDANAAN MODAL KERJA PERUSAHAAN - Miswanto Miswanto (Jurnal Economia, 2012)
Abstract: Policy in Determining and Financing Company’s Working Capital. In funding working capital, a company can use hedging policy, conservative policy, and aggressive policy. In relation to long-term versus short-term financing, temporary versus permanent current assets, and the trade-off between risk and profitability, it can be concluded that when the temporary current assets are financed by short-term financing they have moderate risk and profitability, when the temporary current assets are financed by long-term financing they have low risk and profitability, when the permanent current assets are financed by short-term funding they have high risk and profitability, and when the permanent current assets are financed by long-term financing they have moderate risk-profitability. To measure the performance of the working capital management, the working capital position of the company needs to be analyzed. By using the data presented on the balance sheet and income statement, the company can carry out the analysis of working capital performance using financial ratio analysis on working capital, analysis of the funding sources and use of funding statement, and analysis of the company's cash flow statement. Keywords: liquidity, capital, financing, profitability, and risk  Abstrak: Kebijakan dalam Penentuan dan Pendanaan Modal Kerja Perusahaan. Dalam mendanai modal kerja, perusahaan dapat menggunakan kebijakan hedging, kebijakan konservatif, dan kebijakan agresif. Dalam hubungannya antara pendanaan jangka pendek versus jangka panjang, aktiva lancar temporer versus permanen, dan trade-off antara risiko dan profitabilitas diperoleh kesimpulan bahwa jika aktiva lancar temporer dibiayai dengan pendanaan jangka pendek memiliki risiko dan profitabilitas moderat, jika aktiva lancar temporer dibiayai dengan pendanaan jangka panjang memiliki risiko dan profitabilitas rendah, jika aktiva lancar permanen dibiayai dengan pendanaan jangka pendek memiliki risiko dan profitabilitas tinggi, dan jika aktiva lancar permanen dibiayai dengan pendanaan jangka panjang memiliki risiko dan profitabilitas moderat. Untuk mengukur kinerja manajemen modal kerja, posisi modal kerja perusahaan perlu dianalisis. Dengan menggunakan data yang tersaji pada neraca dan laporan laba rugi, perusahaan dapat melakukan analisis kinerja modal kerja dengan menggunakan analisis rasio keuangan pada modal kerja, analisis pada laporan sumber dan penggunaan dana, dan analisis pada laporan aliran kas perusahaan. Kata kunci: likuiditas, modal, pendanaan, profitabilitas, dan risiko